4 Epidemiology of shoulder dislocations in teeside. (20th December 2017) - Akhtar, MA; Ashton, F; Egglestone, A; David, N; Slade, H; Aveledo, R; Holland, P; Liow, R
Abstract : This study aims to determine the epidemiology of shoulder dislocations in Teeside area to help organise upper limb service provision. A and E records were searched within two large university hospitals covering Teeside population to identify all presentations coded as shoulder dislocation between October 2005 and March 2015. Radiological imaging for all presentations was reviewed for radiological confirmation of dislocation. Census data has been used to calculate estimated catchment population for these hospitals at the mid-point of the study. 3616 A and E presentations were coded for shoulder dislocation. Radiological review confirmed 2686 presentations in 1997 patients with radiological evidence of shoulder dislocation. This included 1858 male presentations (69%), with a male:female ratio of 2.2:1, and a mean age of 42 years. There is a bimodal distribution, with a peak age for male presentation of 20 years and a second peak for female presentation at 86 years. Recurrent dislocation was associated with 916 presentations in 380 patients (19% of identified patients), mean age at presentation of 31 years and a male:female ratio of 3.4:1. Estimated catchment population of 6 98 332 gives an overall incidence of 40.7 per 1 00 000 person-years, and incidence of primary dislocation of 26.9 per 1 00 000 person years. Our incidence of primary shoulder dislocation is marginally higher than that reported in American literature but equivalent to previous Scandinavian data, possibly reflecting differences in healthcare structure. Recurrence rate remains high, suggesting that there is scope for improved management of patients with recurrent shoulder instability.